ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI BENTUK PANGKAT DAN AKAR DI KELAS XI SMA NEGERI 1 ULUSUSUA TAHUNPEMBELAJARAN 2021/2022 - Lisatina Giawa(1); Efrata Gee(2); Darmawan Harefa(3) (Universitas Nias Raya, 2022)
Concept understanding ability is the ability to deeply understand a concept by empowering logical, critical, creative, and inovative minds and being able to account for a concept. Types of qualitative research with a descriptive approach to describe students’ ability to understand mathematical concepts on the material of rank and root forms in class XI SMA Negeri 1 Ulususua. The subject of this study were 14 students who had studied the material with exponents and root forms before. The data collection technique used in this study was the provision of tests and interviews. The result of research and discusion that have been carried out by researchers on each indicator by optaining a percentage can be concluded as follows. 1) Restate a concept 46,72%. 2) Classifying certain object according to their nature 51,78%. 3) Providing examples and not exsamples and not examples of a concept 34,55%. 4) Presenting concept in various forms of mathematical representation 33,98%. 5) Developig necessary or sufficient conditions of a concept 19,34%. 6) Using and itilizing and selecting certain procedures or operations 19,63%. 7) applying concepts or algorithms in problem solving 13,39%. It can be concluded that students understanding of mathematical concepts is still low ini understanding question related to the material of rank and root forms, describing the flow of solutions and problems and aplying the concepts of rankand root form correctly. Researchers suggest that teachers should pay attetion to the ability to understand students’ different concepts. Different so that it can provide a more detailed explanation for students who do not understand the material being taught and this research should be used as comparison material for futher researchers.